Synthesis and investigation of antimicrobial activities of nitrofurazone analogues containing hydrazide-hydrazone moiety - Łukasz Popiołek; Anna Biernasiuk (Elsevier, 2017)
In this research we synthesized and tested for in vitro antimicrobial activity 21 nitrofurazone analogues. The compounds we obtained were identified on the basis of 1H NMR and 13C NMR spectroscopy. The in vitro screening of antimicrobial properties of synthesized compounds revealed a wide spectrum of antimicrobial activity. Compounds 28, 29, 32-43, and 45-48 showed very high bactericidal effect towards Staphylococcus spp. ATTC and Bacillus spp. ATTC (MIC = 0.002-7.81 µg/ml and MBC = 0.002-31.25 µg/ml). The levels of activity of several compounds were far better than those of nitrofurantoin, ciprofloxacin or cefuroxime.